“Prueba ilícita, conflicto de derechos: Derecho a la prueba y la verdad objetiva y la vulneración de los Derechos Fundamentales” - Montero Ulloa, Fernando Adan (2019)
ABSTRACT The present investigation was developed within the scope of Criminal Procedure Law. Having as object of study that "the incorrect application of the criteria on the admission and exclusion of the illegal evidence on the part of the legal operators of the subsystem of judgment, before a conflict of rights: right to the test and to the search of the truth objectively, it violates the fundamental rights of the accused ". For this purpose we have analyzed the sentences issued by the trial judges of the Superior Court of Justice of La Libertad-Trujillo where the defense has urged that the obtaining of the evidence incorporated to the process, were obtained by transgressing the fundamental rights of the accused. . Consequently, the conceptual categories and instruments of this legal discipline were used for this, such as the test, nature and importance of the evidence, its procedural legal concept, the relation between test and truth, object, organ, means and source of evidence, the illegal test, the irregular test, and the comparative law on these institutions, for which we have used for this the data collection through the observation cards, the data processing through the consistency, we have used the analysis and interpretation, as well as the interview for which a questionnaire was formulated, applied to criminal judges, criminal prosecutors and criminal lawyers, thus obtaining not only the criteria on the unlawful evidence but also the knowledge that judges have on this institution when resolving a specific case. We have also made the analysis of the model of criminal process designed by the Political Constitution of the State and its relationship between evidence and Fundamental Law, which forced us, to a certain extent, to resort to conceptual categories of Constitutional Law since we have necessarily analyzed the fundamental rights that are violated through the obtaining or incorporation of the evidence. Taking into account the legal nature of the subject matter of the research carried out, we have had the need to resort to dogmatic criteria of the doctrine and, from a legitimate position, we have been able to contribute. In this order of ideas, we have developed a detailed and sustained theoretical study that has allowed us to arrive at conclusions based on the objectives set by the research carried out. For this reason, having completed the dogmatic study, as well as having analyzed the categories and legal institutions that have been considered, we have been able to determine that the incorrect application of the criteria established for the admission and exclusion of the evidence, in the face of the conflict of rights ; Right to the test and the objective truth, of the judges' judges, when issuing their sentences, violation of the Fundamental Rights of the accused, such as the right to due process, the right to effective procedural protection.